Ward-like Operator in the comma theory - A. Abdurrahman (IJRDO -JOURNAL OF MATHEMATICS, 2019)
The construction of the Ward-like operator of the interacting string …eld theory presented by Witten, in terms of the half-string (comma) oscillator modes, is completed.